Organoleptic Analysis Of The Honeycomb Cake (Kue Sarang Semut) - Faridah, Anni; Jannah, Raudhatul; Marlis, Merisa (Universitas Dr Soetomo, 2020)
The Honeycomb Cake or Caramel Cake or widely known in Indonesia as